Policy Evaluation of the Implementation of the Paskibraka Program at the Provincial Level of DKI Jakarta - Miftackul Huda; Dedeh Maryani; Mutia Rahmah (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study was motivated by the gap between the normative design of Presidential Regulation Number 51 of 2022 and BPIP Regulation Number 3 of 2022 and the implementation of the National Flag Hoisting Troop Program (Paskibraka), including overlapping authority among selection assessors, limitations of the Transparency Application, unequal access for participants from island regions, and the suboptimal follow-up development of Purnapaskibraka Pancasila Ambassador members. The research problem addressed is how to evaluate the policy implementation of the Paskibraka Program at the provincial level in the Special Capital Region of Jakarta. This study employed a qualitative approach within a post-positivist paradigm using a case study method. The evaluation was analyzed using William N. Dunn’s (2018) six evaluation criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. Data were collected through semi-structured in-depth interviews with nine informants selected through purposive sampling from BPIP, the provincial organizing committee, and Purnapaskibraka Pancasila Ambassadors, complemented by document studies. The data were then analyzed using the interactive model of Miles, Huberman, and Saldaña (2014) through source and technique triangulation. The findings indicate that the policy has not been implemented optimally. Effectiveness was achieved only in the formation stage and the execution of flag-hoisting duties, while the four subsequent sub-programs have not yet been implemented. Efficiency has not been achieved because the budget is concentrated on the first two sub-programs, whereas the remaining three follow-up sub-programs receive no allocation. Adequacy and equity have not been fulfilled due to unequal participant access in the Administrative Regency of the Thousand Islands, while responsiveness and appropriateness have only been partially achieved. The study concludes that the policy requires revision regarding the technical regulation of the four follow-up sub-programs. It is recommended to revise Article 11 Paragraph (2) of Presidential Regulation Number 51 of 2022 and Article 21 Paragraph (2) of BPIP Regulation Number 3 of 2022, develop implementation and technical guidelines for the follow-up sub-programs, and incorporate monitoring and sustainability dimensions into the policy evaluation framework for Pancasila ideological development.